2014
DOI: 10.3389/fphy.2014.00046
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution imaging of C-type lectin spatial rearrangement within the dendritic cell plasma membrane at fungal microbe contact sites

Abstract: Dendritic cells express DC-SIGN and CD206, C-type lectins (CTLs) that bind a variety of pathogens and may facilitate pathogen uptake for subsequent antigen presentation. Both proteins form punctate membrane nanodomains (∼80 nm) on naïve cells. We analyzed the spatiotemporal distribution of CTLs following host-fungal particle contact using confocal microscopy and three distinct methods of cluster identification and measurement of receptor clusters in super-resolution datasets: DBSCAN, Pair Correlation and a cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…In addition, our FLIM-FRET results suggested possible intermolecular interactions between Dectin-1 proteins even before stimulation with β-glucan. We considered this possibility carefully because receptor oligomeric states exist in the basal state for some other C-type lectin receptors, such as DCSIGN, DNGR-1, and NKp80 [6871]. However, Dectin-1A does not contain cysteine residues in its stalk region which have been shown to be important in the dimerization of other C-type lectin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our FLIM-FRET results suggested possible intermolecular interactions between Dectin-1 proteins even before stimulation with β-glucan. We considered this possibility carefully because receptor oligomeric states exist in the basal state for some other C-type lectin receptors, such as DCSIGN, DNGR-1, and NKp80 [6871]. However, Dectin-1A does not contain cysteine residues in its stalk region which have been shown to be important in the dimerization of other C-type lectin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…There are other tests to measure spatial heterogeneity such as the Getis G statistic ( Getis & Ord, 1992 ), which includes different normalizations and weighing parameters dependent on molecular spatial position. These differences result in increased sensitivities to certain cluster parameters ( Itano et al., 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the authors identified that removal of extra‐cellular interactions mediated by Galectin‐9 disrupts the meshwork‐like mesoscale pattern of DC‐SIGN receptors, preventing their enrichment in clathrin‐coated patches on the plasma membrane, consequently affecting its endocytosis. The DC‐SIGN receptor is a classic example of tetramers 70 organizing in nano‐clusters (2–3 tetramers) and further incorporated into micron‐scale localization hotspots, driven at least in two different length scales by extra‐cellular domain interactions 66 . Artificially engineering different ABDs to transmembrane proteins with such defined extra‐cellular interactions, in the appropriate cell system, will help understand the interplay or which interactions (extra‐cellular or indirect cytoskeletal barriers) will emerge as a stronger determinant of the nanoscale and emerging mesoscale distribution of the protein.…”
Section: Extra‐cellular Interactions Template Mesoscale Organization mentioning
confidence: 99%